Cost-effectiveness of six months versus 1-year adjuvant trastuzumab in HER2 positive early breast cancer in Egypt. (2nd June 2020) - Elsisi, Gihan Hamdy; Nada, Yousery; Rashad, Noha; Carapinha, João; Noor, Ahmad O.; Almasri, Diena M.; Zaidy, Mostafa Al; Foad, Ahmed; Khaled, Hussien
Abstract: Introduction: Breast cancer is the most prevalent cancer among women in Egypt. Trastuzumab is administered with chemotherapy for patients with HER2-positive advanced breast cancer (HER2 + ve ABC) in the metastatic and adjuvant settings resulting in improved treatment outcomes, and long-term follow-up. Some studies have evaluated whether equivalent outcomes can be achieved with reduced treatment duration. This study evaluates the cost-effectiveness of 6-month versus 1-year trastuzumab treatments from payer perspective over a 10 year time horizon. Methods: A half-cycle corrected Markov model was developed with five mutually exclusive health states; patient with HER2 +ve ABC, disease-free survival (DFS), local or regional relapse, metastatic relapse, and death. A cycle length of 6 months was applied, direct medical costs including cost of treatments, day-care, surgery, health states and follow-up visits were collected, and indirect costs such as lost productivity were not estimated. The transition probabilities and utilities were extracted from published literature, and deterministic sensitivity analyses were conducted. Results: Among the HER2 +ve ABC patient population in Egypt, the total QALYs of the 6-month trastuzumab were estimated to be 2.99 compared with 2.93 for the 1-year trastuzumab which resulted in a difference of 0.06 QALYs. The total costs were EGP 271, 647 ($106, 947) and EGP 381, 248 ($150, 097), respectively. These costs yielded an ICER of –109, 600 EGP/QALY (–43, 149 $/QALY) for the 6-month trastuzumab. The 6-month trastuzumab is a dominant strategy when compared to 1-year trastuzumab, resulting in improved effectiveness at a reduced cost. All analyses results confirmed the dominance of 6-month trastuzumab and our model robustness. Conclusions: This study concluded that 6-month trastuzumab is a cost-effective option when compared to 1-year trastuzumab in patients with HER2 +ve ABC in Egypt. Our findings provide health care decision makers with additional insights to best allocate available resources concurrently with the improvement of the Egyptian patient's outcomes.